2017
DOI: 10.1016/j.jrras.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patients X-ray doses at three government hospitals in Duhok city lacking requirements of effective quality control

Abstract: To cite this article: Haval Y. Yacoob (Assistant Prof of Radiation Biophysics) & Hariwan A. Mohammed (Assistant Physics) (2017) Assessment of patients X-ray doses at three government hospitals in Duhok city lacking requirements of effective quality control,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Tube filtration removes lower energy X-rays from the X-ray spectrum which otherwise would have caused unnecessary radiation dose to patients and degrade image quality. This observation was consistent with similar observation by Sezdi (2011) who reported that tube filtration could also affect tube output of X-ray equipment (25) . It was observed that kVp has quadratic effect on the tube output therefore, difference in measured kVp from different equipment would result in variations in the tube output.…”
Section: Discussionsupporting
confidence: 93%
“…Tube filtration removes lower energy X-rays from the X-ray spectrum which otherwise would have caused unnecessary radiation dose to patients and degrade image quality. This observation was consistent with similar observation by Sezdi (2011) who reported that tube filtration could also affect tube output of X-ray equipment (25) . It was observed that kVp has quadratic effect on the tube output therefore, difference in measured kVp from different equipment would result in variations in the tube output.…”
Section: Discussionsupporting
confidence: 93%
“…The consequences were high patient dose, image distortion, clipping of important anatomy, and grid cut-off among others [9]. A similar study reported patient dose reduction in the range of 31-77% for equipment having quality control assessment, while none calibrated equipment increased patient dose up to a factor of 1-5 times more than IAEA guidance level [13]. The study by Ngaile et al confirmed that the lowering of mAs is suitable for x-ray equipment with higher timer reproducibility, while an increase in tube potential works well in equipment with high accuracy and voltage consistency [14].…”
Section: Introductionmentioning
confidence: 95%
“…Evidence has shown that DRLs should form part of a quality control (QC) programme [22] . DRLs should be recalculated quarterly and compared to the baseline values proposed by the AAPM Imaging Physics Committee Task Group [23] .…”
Section: Pidrls Contribution To Image Qualitymentioning
confidence: 99%